NEW BIOSTRATIGRAPHIC DATA FROM THE REITANO FLYSCH AUCT. (SICILY, ITALY): A KEY TO A REVISED STRATIGRAPHY OF THE SICILIDE UNITS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The study of palynomorphs and calcareous nannofossils recovered from the volcano-arenitic succession outcropping at Troina and Cerami (Sicily) documents Rupelian assemblages comparable to those published for the Tusa Tuffite. This new evidence, combined with petrographic, geochemical and sedimentological affinities documented in the literature, eventually proves the genetic relationships between these units. Accordingly, the new name Troina-Tusa Formation is proposed to include all these lower Oligocene volcano-sedimentary units and to replace inappropriate names formerly used. The Troina-Tusa Formation conformably lies on a mixed siliciclastic-carbonate turbidite succession, lacking volcanic detritus, reported in the literature with different names (Polizzi Formation, Varicoloured Shales, Troina-Tusa Flysch) and different ages (ranging from Eocene to Early Miocene). Palynomorphs and nannofossils recovered from its uppermost part, indicate an earliest Oligocene age. The denomination Polizzi Formation is recommended for this unit that includes also the Varicoloured Shales (Eocene-basal Oligocene). The appearance of conglomerates and volcano-arenites in the basal portion of the Troina-Tusa Formation, immediately above the top of the Polizzi Formation, marks a sudden reorganization of the Rupelian depositional systems related to the rise and erosion of a volcanic belt. Apparently, no biostratigraphically detectable hiatus is associated to this boundary. Differences in the composition of sandstones, sedimentary features and relationships with the substratum do exist between the ‘internal’ Reitano Flysch, outcropping in the type-area on the northern slope of the Nebrodi Mountains, and the volcano-arenitic successions of Cerami and Troina, reported by some authors as ‘external’ Reitano Flysch. These differences are widely documented in the literature, where the ‘internal’ Reitano Flysch is shown to lack volcanic detritus and to rest unconformably on the deformed Monte Soro Flysch. Since the definition of the Troina-Tusa Formation now includes the external outcrops (Cerami, Troina, Ancipa Lake), the adjectives ‘internal’ and ‘external’ become disused, and the name Reitano Flysch is restricted to the successions lacking volcanic detritus exposed in the type-area of Reitano, Pettineo, Caronia and Capizzi. Palynomorphs and nannofossils recovered from the Pettineo section, suggest a Rupelian age also for the Reitano Flysch.
Keywords: Biostratigraphy; Organic-walled dinoflagellate cysts; Calcareous nannofossils; Turbidites; Volcano-arenites; Rupelian; Sicily; Italy